(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article investigates the semantic monosemy and lexical expression of behavioral verbs within the Uzbek language. Behavioral verbs, which denote habitual, characteristic actions or mannerisms associated with human behavior, often display a notable semantic stability characterized by monosemy — having a single, unambiguous meaning. By analyzing the morphological and semantic properties of these verbs in Uzbek, this study explores how monosemy manifests and what implications it holds for lexical representation and semantic theory.